Pengembangan Soal Berpikir Kritis Menggunakan Software iSpring QuizMaker Sebagai Media Display Pada Materi Kesetimbangan Ion dan pH Larutan Garam: DEVELOPMENT OF CRITICAL THINKING PROBLEMS TEST USING iSPRING QUIZMAKER SOFTWARE AS A DISPLAY MEDIA ON ION EQUILIBRIUM AND pH OF SALT SOLUTION MATERIALS - Melly Shintia Melcin; Maria Erna; Sri Haryati (UIN Mataram, 2021)
This study aims to produce an evaluation instrumen for critical thinking using the software iSpring QuizMaker on ion balance material and the pH of a valid salt solution according to material and media experts, knowing the validity, reliability, level of difficulty, discriminating power and user response. This study uses a research and development (R&D) design with the Plomp model. The research subjects consisted of 3 teachers and 30 students of class XI SMAN 8 Pekanbaru, SMAN 12 Pekanbaru and MAN 1 Pekanbaru. Data collection techniques are carried out by literature studies and field studies. The research data was obtained from the validation results of two material validators and two media validators as well as user trials. The results of the validation by the material validator based on the material aspect were 90.67%, the construction aspect was 87.33% and the language aspect was 90.89%. According to media validators based on aspects of substance content 100%, learning design 100%, display (visual communication) 98% and software utilization 97.14%. The results of the item analysis show that 15 items are valid, have very high reliability, have 5 items of